The relationships between job satisfaction, working relationship and human resource management practices on turnover intention among safety and health officers in the construction industry - Aisha, Warshaf (2017)
Aim: The overall objective of this study will be to identify relationship of job satisfaction, working relationship and human resources management practice on turnover intention among safety and health officer in construction industry. Literature review: A collection of literature related to Safety and Health Officer and the construction in Malaysia, turnover intention, job satisfaction, working relationship and human resources management practices. Methodology: The study design used is cross-sectional study which involves both descriptive statistic and inferential statistic. A pilot study of 30 respondents is carried out to test the reliability. A sample of 205 Safety and Health Officer (SHO) working in construction industry across state of Selangor Darul Ehsan. Respondent answer one set of self-administrated questionnaire consisting of demographic items, a job satisfaction, working relationship, human resources management practices survey as well as a question represent the intention to quit via online platform. Result and Discussion: This study provides the concept of how will these three independent factors will affect employee turnover and more data, findings and comparisons will be presented in future journal on selecting the best factors that have impact on employee turnover the most. All independent variables had significant negative relationship towards intention to quit with work relationship is the highest predictor variable as Beta value under standardized coefficient scored (0.244) if compare to job satisfaction and human resource management practices are (0.231) and (0.224) respectively. Conclusion and Recommendation: In conclusion, this research show medium significant intention to leave and there is essential need to conduct further studies.